Continuity of Life After Retirement: Perspectives Among Selected Public School Educators of Nueva Ecija (American Journal of Interdisciplinary Research and Innovation, 2023)
This research determined the perspectives of retiring teachers about life after retirement. A researcher-made survey tool was developed using a descriptive correlational method and went through the standard procedure of validation and reliability, gaining a 0.945 Cronbach’s Alpha mark. The tool was administered to 148 retiring teachers. Responses were statistically treated using frequency, percentage, mean and Pearson r correlations. Results revealed that the majority of the 148 respondents fell in 50-55 bracket while 13 belong to 61-65. Of the same total, 132 were female and 16 were male. In terms of civil status, 126 were married, and only two (2) were single. In terms of monthly income, 47 representing the majority has 21,000-30,000 monthly incomes in pesos. The educational attainment with the highest number was bachelors degree with masteral units, had 101 respondents. Five (5) were in an ongoing doctorate course, the lowest in number. Teachers who were about to retire have assessed themselves having good health condition both physical and mental functioning. Further, when it comes to life continuity after retirement, they assured themselves of absence of disease and disease-related disability. It was also determined that in life continuity perspective, their topmost choice was “they will uphold the values of being an educator (M=3.53)”. Relevant to life course perspective, they banked the intention that “they will be active in church (M=3.55)” as their preference and in terms of life role perspective, they opted to “they will take care of their family, especially their grandchildren (M=3.61)” as their priority role. Significant relations were also established in reference to their demographic profile and the domains of life continuity theory. It was recommended that teachers themselves must be more cautious and diligent as they plan and prepare for their retirement. Future researchers were also encouraged to pursue similar topics for further scrutiny of life after retirement.